2013
DOI: 10.7773/cm.v39i1.2176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors on the spawning of sciaenids in the Buenos Aires Coastal Zone, Argentina

Abstract: ABSTRACT. The fish community in coastal waters of the Buenos Aires Province is dominated by seven sciaenid species: Micropogonias furnieri, Cynoscion guatucupa, Macrodon ancylodon, Pogonias cromis, Umbrina canosai, Paralonchurus brasiliensis, and Menticirrhus americanus. The relation between sciaenid spawning females and environmental factors was examined in order to describe the spawning strategy of these species in Argentine coastal waters. Sciaenid species were classified into three groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…Coward et al (2002) reported that low salinities cause a loss of gamete viability and the death of embryos in fish species that spawn in marine habitats, due to a deficient regulation of cellular osmolarity. In contrast with this apparent incapacity of the snooks to spawn in FW, the euryhaline Micropogonias furnieri spawns in different salinity environments and favors the success of the progeny by providing a valuable strategy for the use of resources and the possibility of colonizing new habitats (Militelli et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coward et al (2002) reported that low salinities cause a loss of gamete viability and the death of embryos in fish species that spawn in marine habitats, due to a deficient regulation of cellular osmolarity. In contrast with this apparent incapacity of the snooks to spawn in FW, the euryhaline Micropogonias furnieri spawns in different salinity environments and favors the success of the progeny by providing a valuable strategy for the use of resources and the possibility of colonizing new habitats (Militelli et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Coward et al (2002) indicaron que la baja salinidad causa la pérdida de la viabilidad de los gametos y la muerte de los embriones de especies de peces que desovan en hábitats marinos, debido a deficiencias en la regulación de la osmolaridad celular. En contraste con esta aparente incapacidad de los robalos para desovar en ambientes dulceacuícolas, el pez eurihalino Micropogonias furnieri desova en ambientes de diferente salinidad, con lo que favorece el éxito de la progenie al proveer de una estrategia valiosa en el aprovechamiento de recursos y la posibilidad de colonizar nuevos hábitats (Militelli et al 2013).…”
Section: Acknowledgmentsunclassified
“…El Río de la Plata y la Zona Común de Pesca Argentino-Uruguaya (ZCPAU) representa un ambiente muy productivo, que sostiene pesquerías artesanales y costeras tanto en la Argentina como en Uruguay (Acha et al 2008). En esta área también se llevan a cabo pesquerías demersales multiespecíficas asociadas a diferentes tipos de flotas comerciales (Militelli et al 2013), así como a stocks de especies costeras que utilizan la zona como área de reproducción y cría (Mianzan et al 2001;Jaureguizar et al 2003).…”
Section: Introductionunclassified
“…Dicha zona presenta profundidades menores a 50 m y se caracteriza por condiciones oceanográficas particulares, determinadas principalmente por un frente estuarino paralelo a la costa (Martos et al 2005; Auad y Martos 2012). Durante la época estival la zona de ER es de gran relevancia como área de cría de un gran número de especies de peces de interés comercial y concentración de juveniles, como así también es una zona de desove multiespecífico (Macchi y Acha 1998; Sardiña y López Cazorla 2005; Ruarte et al 2009;Militelli et al 2013;Rodrigues et al 2013). En esta región se desarrolla además una pesquería dirigida al ensamble demersal costero que incluye el desembarque de unas 30 especies de peces óseos y cartilaginosos capturadas por pesca dirigida o incidental y denominado comercialmente Variado Costero (Carozza et al 2001).…”
Section: Introductionunclassified